Fabrication Of Aquaponic System For Integrated Freshwater Fish And Vegetables Cultivation - Yohandri Yohandri (Pelita Eksakta, 2020)
The Community Partnership Program (PKM) activity has been carried out in Nagari Sunua, Padang Pariaman District, West Sumatra. As for Sunua's diversity, many young people drop out of school and do not have permanent jobs. This activity aims to provide training in the manufacture of aquaponic systems that combine freshwater fish cultivation with vegetable cultivation simultaneously. Partners will be given training on how to use freshwater aquaculture pond water to grow vegetables. Pool water will be flowed in the pipes where the vegetable seeds are grown. Pond water becomes fertilizer and nutrition for vegetables. Water that has passed through vegetables in the next pipe will be flowed back into the pond. This aquaponic cultivation pattern is very beneficial because it can produce vegetables and fish simultaneously in one activity. This can be a new type of business for partner groups that have not. In general, these activities can be carried out well and increase the knowledge and skills of the members of the partners involved.